Hubungan Pola Makan dengan Kejadian Gastritis di Puskesmas Marina Permai Kota Palangka Raya: The Correlation Between Dietary Habits with Gastritis at Public Health Center (Puskesmas) of Marina Permai, Palangka Raya City - Andreas Andreas; Lensi Natalia Tambunan; Eva Prilelli Baringbing (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Gastritis is a disease that can interfere the activities and can be fatal if not treated properly. Based on data from the health office of Palangka Raya city in 2017, cases of gastritis reached 7,554 cases and ranked third in the top 10 diseases in all public health centers in Palangka Raya city. At the public health center (Puskesmas) of Marina Permai, there were 306 cases of gastritis in 2019, and in 2020 it rose to 317 cases. This study aimed to determine the correlation between dietary habits and the incidence of gastritis in patients in the Puskesmas of Marina Permai. The method used in this study is cross-sectional research with a population of 93 people and a sample of 75 respondents. Moreover, the sampling technique used is purposive sampling with a chi-square statistical test. The result of the study shows a (p-value) of 0.008 with a significant degree of p <0.05, which means that there is a significant correlation between dietary habits and the incidence of gastritis. Based on the result of the study that there is a correlation between dietary habits and the incidence of gastritis in the area of Puskesmas of Marina Permai, it is hoped that the respondent's diet will be improved to reduce the risk of developing gastritis.